Pemanfaatan Artificial Intelligence untuk Peningkatan Kompetensi Guru Bahasa Indonesia SMP - Yusra Dewi; Dimas Anugrah Adiyadmo; Deri Rachmad Pratama; Sophia Rachmawati; Priyanto Priyanto (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
This community service program aims to enhance the competence of junior high school Indonesian language teachers in Tanjung Jabung Timur Regency in utilizing Artificial Intelligence (AI) for developing learning assessment instruments. In the era of digital transformation, teachers are required to produce assessment tools that are aligned with the curriculum, promote Higher Order Thinking Skills (HOTS), and can be developed efficiently. However, teachers often encounter challenges in creating varied, innovative, and high-quality test items within limited time constraints. The training was conducted using a participatory approach involving concept dissemination, hands-on practice with AI (ChatGPT), simulation of item construction, and reflective evaluation sessions. The results show that participants were enthusiastic and actively engaged in using AI, producing more diverse test items, although unstable internet connections were noted as a technical limitation. The novelty of this activity lies in the integration of AI technology into the design of Indonesian language evaluation instruments, thereby strengthening teachers’ digital literacy and supporting the digital transformation of education in the region. The implications include opportunities for further collaboration in curriculum development, AI-based item bank creation, and broader technology integration in teaching practices.